2004
DOI: 10.1093/jee/97.2.374
|View full text |Cite
|
Sign up to set email alerts
|

Damage Loss Assessment and Control of the Cereal Leaf Beetle (Coleoptera: Chrysomelidae) in Winter Wheat

Abstract: Cereal leaf beetle, Oulema melanopus (L.), invaded northern Alabama and Georgia more than a decade ago and since has become an economic pest of winter wheat and other cereal crops in the southeastern United States. A series of trials was conducted beginning in 1995 to determine optimal rate and timing of applications of selected foliar insecticides for managing cereal leaf beetle in soft red winter wheat. These trials, cage studies with larvae, and a manual defoliation experiment were used to provide informati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
28
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(31 citation statements)
references
References 13 publications
3
28
0
Order By: Relevance
“…Grain yield losses due to flag leaf removal were 25% and 21% for main stems and totality of tillers, respectively. This result supports the importance of the flag leaf as an important organ contributing to cereal grain yield and that any damage to its green leaf area would generate significant yield losses (Sharma et al 2003;Buntin et al 2004;Jebbouj and El Yousfi 2006). Removing upper leaves and consequently measuring losses in grain yield, scientists logically attribute the magnitude of losses to the contribution to grain yield by these defoliated leaves.…”
Section: Discussionsupporting
confidence: 61%
See 3 more Smart Citations
“…Grain yield losses due to flag leaf removal were 25% and 21% for main stems and totality of tillers, respectively. This result supports the importance of the flag leaf as an important organ contributing to cereal grain yield and that any damage to its green leaf area would generate significant yield losses (Sharma et al 2003;Buntin et al 2004;Jebbouj and El Yousfi 2006). Removing upper leaves and consequently measuring losses in grain yield, scientists logically attribute the magnitude of losses to the contribution to grain yield by these defoliated leaves.…”
Section: Discussionsupporting
confidence: 61%
“…Consequently, this reduction mainly arises from a decreasing number of fertile spikelets affected by the disease (Buntin et al 2004). This study also demonstrated that removing all leaves, followed by flag leaf removal, had the greatest impact on wheat yield components during the flag leaf and spike emergence stages.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A cereal leaf beetle (Oulema melanopus L.) represents the most important wheat pest in many European countries (Dimitrijevic et al, 1999), and has become an economic pest of winter wheat and other cereal crops in the United States (Ihrig et al, 2001;Buntin et al, 2004). Also, fungal growth can substantially damage food and animal feeds; these forms of food damage can be manifested as general spoilage, reduced nutritional quality, mycotoxin formation, and production of (potentially allergenic) spores (Schnurer et al, 1999).…”
Section: Introductionmentioning
confidence: 99%